HOXA11 antisense long noncoding RNA (HOXA11‐AS): A promising lncRNA in human cancers - Cheng‐Wei Lu; Dan‐Dan Zhou; Tian Xie; Ji‐Long Hao; Om Prakash Pant; Cheng‐Bo Lu; Xiu‐Fen Liu (Cancer Medicine)
Abstract The cancers are the leading cause of disease‐related deaths worldwide with a high risk of morbidity and mortality. Long noncoding RNAs (lncRNAs) play a critical role in a wide range of biological processes, including tumorigenesis. HOXA11‐AS (NCRNA00076), the antisense strands of HOXA11 gene, was initially revealed in a mouse embryonic cDNA library in 2009 and it was a fairly novel lncRNA. This review summarized the advanced research progression concerning the expression and role of HOXA11‐AS in different human malignancies. The expression of HOXA11‐AS is aberrantly altered in many cancers, either as a tumor suppressor or as a tumor accelerator. The different underlying mechanism of HOXA11‐AS in different cancers (including, nonsmall cell lung cancers, osteosarcoma, uveal melanoma, glioma, hepatocellular carcinoma, gastric cancer, breast cancer, cervical cancer, ovarian cancer, colorectal cancer, ovarian cancer, and glioblastoma) was also detailed. These findings lead us to conclude that HOXA11‐AS participate in the complex network of cancers and plays an important role in the tumorigenesis and progression. Functional HOXA11‐AS could be a promising biomarker for early detection as well as prognosis evaluation in cancer patients. Future HOXA11‐AS‐targeted intervention may become a valuable novel therapeutic tool, improving the clinical management of cancers.